2013
DOI: 10.1021/bi4003343
|View full text |Cite
|
Sign up to set email alerts
|

The Orphan Protein Bis-γ-glutamylcystine Reductase Joins the Pyridine Nucleotide Disulfide Reductase Family

Abstract: Facile DNA sequencing became possible decades after many enzymes had been purified and characterized. Consequently, there are still “orphan” enyzmes whose activity is known but the genes that encode them have not been identified. Identification of the genes encoding orphan enzymes is important because it allows correct annotation of genes of unknown function or with mis-assigned function. Bis-γ-glutamylcystine reductase (GCR) is an orphan protein that was purified in 1988. This enzyme catalyzes the reduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…42,43 IYD revealed an origin that is much more ancient than would be anticipated by its iodide salvage activity in mammals and may indicate requirements for iodide or iodinated molecules in most multicellular organisms. The enzyme is now ready to join the ranks of other TH-associated proteins in describing the evolution of TH signaling.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…42,43 IYD revealed an origin that is much more ancient than would be anticipated by its iodide salvage activity in mammals and may indicate requirements for iodide or iodinated molecules in most multicellular organisms. The enzyme is now ready to join the ranks of other TH-associated proteins in describing the evolution of TH signaling.…”
Section: Resultsmentioning
confidence: 96%
“…The successful identification of a specialized enzyme such as IYD in diverse organisms demonstrates the importance of experimental data to support the functional assignment of a flavoprotein. 42,43 IYD revealed an origin that is much more ancient than would be anticipated by its iodide salvage activity in mammals and may indicate requirements for iodide or iodinated molecules in most multicellular organisms. The enzyme is now ready to join the ranks of other TH-associated proteins in describing the evolution of TH signaling.…”
Section: Discussionmentioning
confidence: 98%
“…GSH1 produces l -γ-glutamylcysteine, the only known cellular role of which is as a precursor of glutathione. The only known exception is that Halobacteria use l -γ-glutamylcysteine as an antioxidant through the enzyme bis-γ-glutamylcysteine reductase (Kim and Copley 2013). We did not detect homologs of this enzyme in any of the fornicata genomes.…”
Section: Resultsmentioning
confidence: 99%
“…Kim and Copley (2013) [33] further expressed an H. salinarum (sp. NRC-1) gene annotated as mercuric reductase (MerA) in Escherichia coli and demonstrated that the enzyme had robust NADPH-dependent GCR activity but no mercuric reductase activity [33]. The genomes of most, but not all, haloarchaea for which whole genome sequences are available have homologues that are at least 50% identical to GCR (UniRef 50 of UniProt Q9HSN0).…”
Section: Glutathione and γ-Glutamylcysteinementioning
confidence: 98%
“…While the gene was not identified in this early work, Sundquist and Fahey provided evidence in H. salinarum for a γGC reductase (GCR) that was distinct from dihydrolipoamide dehydrogenase (DHD), the E3 component that oxidizes the thiol groups of dihydrolipoamide (Lip-(SH) 2 ) to lipoamide (Lip-(S) 2 ) in α-keto acid dehydrogenase complexes [31,32]. Kim and Copley (2013) [33] further expressed an H. salinarum (sp. NRC-1) gene annotated as mercuric reductase (MerA) in Escherichia coli and demonstrated that the enzyme had robust NADPH-dependent GCR activity but no mercuric reductase activity [33].…”
Section: Glutathione and γ-Glutamylcysteinementioning
confidence: 99%